Determinant Models of Sharia Financial Literacy Muslim Students in Indonesia: A Multidimensional Approach - Sihotang, Mutiah Khaira; Hasanah, Uswah; Hayati, Isra (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The Sharia financial institutions in Indonesia, especially the city of Medan, are growing and continuing to compete with the existing conventional finance institutions. This should be combined with public knowledge of the sharia financial institutions. Therefore, there is a need for education toward the financial literature of sharia for the whole layer of society, from parents to children. This research aims to find out the determination factor of the financial literature of sharia in muslim students in indonesia. The dependent variables used in this study are parent income, student learning achievements, information and religious sources with sharia financial literacy as independent variables. Sampling in this study uses purposive sampling. The population in this study was the muslim students who were in the Medan city, Indonesia. The study used a quantitative approach where primary data was obtained through the dissemination of the questionnaire, with the total sample of 180 people. The study was tested for validity and reliability. The data is then analyzed with double regression. All phases of testing and data analysis are carried out with the help of SPSS. The results of this study stated that the variable learning performance and information sources have a significant influence on the financial literacy of muslim students in the city of Medan, Indonesia. Income and religious variables do not affect student financial literacy. This is seen from the t-test with a significance value > 0.05.